The Effect of the Jigsaw Cooperative Learning Model on Improving Communication Skills of Fourth-Grade Students at Sd Inpres 2 Tondo - Nurliyan Nurliyan; Abdul Rahman; Nuraini Nuraini; Nashrullah Nashrullah; Eva Setya Rini (Journal of Educational Sciences, 2026)
Communication skills are essential competencies that support students’ academic success and social interaction in the learning process. However, field observations indicated that fourth-grade students at SD Inpres 2 Tondo showed low communication skills, particularly in expressing opinions and participating actively in classroom discussions. This study aimed to examine the effect of the Jigsaw cooperative learning model on improving students’ communication skills. The research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group pretest–posttest design. The participants consisted of 38 fourth-grade students divided into an experimental class and a control class. The experimental class was taught using the Jigsaw cooperative learning model, while the control class received conventional instruction. Data were collected through communication skills tests and observation sheets and analyzed using descriptive analysis, normalized gain, and independent sample t-test. The results showed that students taught using the Jigsaw model achieved higher posttest scores and better communication skill performance compared to those taught using conventional methods. These findings indicate that the Jigsaw cooperative learning model is effective in enhancing elementary school students’ communication skills and can be applied as an alternative instructional strategy in language learning.